2021
DOI: 10.3346/jkms.2021.36.e161
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Olfactory Dysfunction in COVID-19 Patients

Abstract: Background The aim of this study was to evaluate the subjective and objective olfactory function in coronavirus disease 2019 (COVID-19) patients and the effect of olfactory training. Methods A prospective cohort study was performed in 53 patients who recovered from COVID-19 and visited our tertiary hospital. Subjective olfactory function was evaluated using the 11-point Likert scale (0–10) and the Korean version of the Questionnaire of Olfactory Disorders (QOD). Objecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…COVID-19-related OD was previously considered to recover on its own with progress in time. However, recent studies revealed that nearly 50% of patients had OD more than 3 months after COVID-19 based on subjective and objective evaluation ( Bussière et al, 2021 ; Seo et al, 2021 ). OD affected daily life activities ( Temmel et al, 2002 ) and had a negative influence on psychological status ( Valsamidis et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…COVID-19-related OD was previously considered to recover on its own with progress in time. However, recent studies revealed that nearly 50% of patients had OD more than 3 months after COVID-19 based on subjective and objective evaluation ( Bussière et al, 2021 ; Seo et al, 2021 ). OD affected daily life activities ( Temmel et al, 2002 ) and had a negative influence on psychological status ( Valsamidis et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported the recovery from OD in many patients within a month following the onset of OD ( D’Ascanio et al, 2021 ; Lechien et al, 2020 ). However, some studies have reported long-term persistence of OD ( Bertlich et al, 2021 ; Bussière et al, 2021 ; Seo et al, 2021 ). OD results in reduced quality of life ( Temmel et al, 2002 ); however, effective treatments are limited ( Addison et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In another study, recently published by our authors, regarding the effect of olfactory training in patients with olfactory dysfunction even after three months of symptom onset, 10 patients underwent olfactory training for 8 weeks using four Korean odorants: pine, peppermint, cinnamon, and lemon. It was found that the objective olfactory function score using the Cross-Cultural Smell Identification Test (CC-SIT) was significantly increased after olfactory training, with 70% of patients reporting a recovery to normal olfactory function [ 25 ].…”
Section: Treatment Of Olfactory Dysfunctionmentioning
confidence: 99%
“…Several studies have reported the clinical course of COVID-19-associated olfactory and gustatory dysfunctions [ 21 , 22 , 23 , 24 , 25 , 26 ]. According to these results, approximately 8.57–25% of these patients did not have improved subjective olfactory function at 1–2 months after symptom onset, and 11.2% did not have improved subjective olfactory dysfunction at 6 months after symptom onset.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation